Methodological orientations directed the physical rehabilitation and speech therapy in cases of dysarthria (Original) (Revista científica Olimpia, 2021)
At present, it is common to observe students "different from others", by their uncoordinated walking, by their exaggerated movements with their arms and hands, by their constant grimaces and by their difficulty in eating and talking. All this symptomatology coincides with a lesion in the central and peripheral nervous system that brings with it difficulties in the act of speech, dysarthria. Language disorder that is the object of study by specialists such as physiotherapist (Physical Education teacher) and speech therapists. If these last two work together, the student will gain in his rehabilitation. Reason for which the authors of the present article designed the methodological orientations directed the physical rehabilitation and speech therapy in cases of dysarthria.
Keywords: dysarthria, methodological orientations, physical rehabilitation, speech therapy